Effects of split position on the performance of a compact broadband printed dipole antenna with split-ring resonators - Kedze, Kam Eucharist; Wang, Heesu; Park, Ikmo (Journal of Electromagnetic Engineering and Science, 2019)
This paper presents the effects of the position of the split of a split-ring resonator (SRR) on the performance of a composite broadband printed dipole antenna. The antenna is made of two printed dipole arms enclosed by two rectangular and identically printed SRRs. One dipole arm and the SRR are printed on the top side of the substrate, while the other dipole arm and SRR are printed on the bottom side of the same substrate. By changing the position of the split on the SRR, different antenna characteristic values are obtained, namely, for impedance bandwidth and radiation patterns. The split position is thus a critical parameter in antenna design, because it influences the antenna's major performance immensely. Different split positions and their consequences for antenna performance are demonstrated and discussed. The antenna generates linearly polarized radiations, and it is computationally characterized for broadband characteristics. The optimized compact antenna has overall dimensions of 9.6 mm × 74.4 mm × 0.508 mm (0.06λ × 0.469λ × 0.0032λ at 1.895 GHz) with a measured fractional bandwidth of 60.31% (1.32 to 2.46 GHz for |S11| < -10 dB) and a radiation efficiency of > 88%.
Keywords: Broadband; Compact Size; Composite Antenna; Dipole Antenna; Split Ring Resonator (SRR)